An efficient NIR-to-NIR signal-based LRET system for homogeneous competitive immunoassay - Kang, Dongkyu; Lee, Seok; Shin, Heewon; Pyun, Jaechul; Lee, Joonseok (ELSEVIER ADVANCED TECHNOLOGY, 2020)
Upconversion nanoparticles (UCNPs) are promising materials for biological applications based on luminescence resonance energy transfer (LRET). In contrast to classical RET donors such as quantum dots, gold nanoparticles, UCNPs can emit near-infrared (NIR) upon the NIR irradiation, which provides enhanced signal-to-noise due to strong penetration and low autofluorescence in the NIR region known as the diagnostic window. Here we report the first efficient NIR-to-NIR signal-based LRET system for the detection of progesterone, chosen as a proof-ofconcept target, via homogeneous competitive immunoassay. To enhance the efficiency of LRET, we constructed inert-core/active-shell/inert-ultrathin shell UCNPs (NaYF4@NaYF4:Yb,Tm@NaYF4) as an LRET donor and a compact progesterone/horseradish peroxidase/IRdyeQC-1 (P-HRP-dyes) complex as an LRET acceptor. The designed donor and acceptor showed significantly improved LRET efficiencies (95% and 85% for donor and acceptor, respectively) compared with conventional donor and acceptor (70% and 50%, respectively). Using the developed NIR-to-NIR LRET system, progesterone was successfully detected with a background-free signal and low limit of detection (1.36 pg/ml in ten-fold diluted human serum). We believe that the efficient NIR-to-NIR signal-based LRET system developed here has potential as a simple probe for homogeneous competitive immunoassay, with the ability to rapidly detect biomarkers.
Keywords: UP-CONVERSION NANOPARTICLES; RESONANCE ENERGY-TRANSFER; FRET; LUMINESCENCE; RANGE